2007
DOI: 10.1073/pnas.0701826104
|View full text |Cite
|
Sign up to set email alerts
|

Gamma oscillations dynamically couple hippocampal CA3 and CA1 regions during memory task performance

Abstract: The hippocampal formation is believed to be critical for the encoding, consolidation, and retrieval of episodic memories. Yet, how these processes are supported by the anatomically diverse hippocampal networks is still unknown. To examine this issue, we tested rats in a hippocampus-dependent delayed spatial alternation task on a modified T maze while simultaneously recording local field potentials from dendritic and somatic layers of the dentate gyrus, CA3, and CA1 regions by using high-density, 96-site silico… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
370
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 398 publications
(406 citation statements)
references
References 56 publications
24
370
3
Order By: Relevance
“…Other corroborating observations come from the increased c-FOS activity in the hippocampus of B6 mice, which was largest for the drug that also induced the largest increase in gamma activity; that is YKP10A. Gamma activity in the hippocampus is thought to coordinate CA3 and CA1 networks during memory task performance (Montgomery and Buzsaki, 2007) in which c-FOS reactivity was exclusively found.…”
Section: Drug Effects On the Waking Eegsupporting
confidence: 53%
“…Other corroborating observations come from the increased c-FOS activity in the hippocampus of B6 mice, which was largest for the drug that also induced the largest increase in gamma activity; that is YKP10A. Gamma activity in the hippocampus is thought to coordinate CA3 and CA1 networks during memory task performance (Montgomery and Buzsaki, 2007) in which c-FOS reactivity was exclusively found.…”
Section: Drug Effects On the Waking Eegsupporting
confidence: 53%
“…9,11,29 Moreover, the precise timing of action potentials is central for use-dependent synaptic plasticity and, thus, supports learning and memory formation. 13,20,30,31 In neuronal networks in vivo, gamma oscillations occur transiently on the hundred millisecond time scale upon sensory input or during specific cognitive tasks. In the human brain and dependent on the task, however, they can last for prolonged times in the range of minutes.…”
Section: Gamma Oscillations and Cortical Information Processingmentioning
confidence: 99%
“…16,41 They can occur in the presence or in the absence of theta oscillations, 40,41 similar to the pattern of gamma oscillations in vivo. 8,30,48 Alternative models are based on the induction of transient phases of gamma oscillations: local tetanic electrical stimulation, topic application of potassium-rich solution, or application of metabotropic glutamate receptor agonists. 16,38,49 However, electrical stimulation of neuronal tissue can only partially mimic the features of naturally occurring network oscillations.…”
Section: Gamma Oscillations and Cortical Information Processingmentioning
confidence: 99%
“…More recently, cortical inhibitory networks have also been proposed to play a critical role in the generation of faster activities that include oscillations in the low (i.e, beta-gamma oscillations at 20-80 Hz) and high frequency range (>80 Hz, so called ripples) (Buzsáki et al, 1992). Interestingly, both beta-gamma rhythms and ripples occurring in cortical areas (Gray et al, 1989;Murthy and Fetz, 1992;Singer and Gray, 1995), including those of the limbic system Chrobak and Buzsáki, 1998;Csicsvari et al, 1999Csicsvari et al, , 2003, have been implicated in higher brain processes such as attention, sensorimotor integration, consciousness, learning and memory (Girardeau et al, 2009;Montgomery and Buzsáki, 2007). Therefore, it has been suggested that these oscillatory rhythms represent the basic neuronal processing state of the brain (Basar et al, 1999).…”
Section: Role Of Gaba a Receptors In Neuronal Network Oscillationsmentioning
confidence: 99%